Plato's ""Sophist"" Revisited. - Robinson, Thomas M. (Trends in classics. Supplementary volumes., 2013)
This book consists of a selection of papers which throw new light on old problems in one of Plato's most difficult dialogues. The first set of papers deals with definitions of sophistry from different perspectives (T. Robinson, F. Casadesús, J. Monserrat-P. Sandoval, A. Bernabé, M. Narcy and K. Dorter). In the central section E. Hülsz, D. O'Brien, B. Bossi, P. Mesquita and N. Cordero consider the problem of being and relative non-being with regard to Heraclitus and the legacy of Parmenides. The final section with papers by F. Fronterotta, J. de Garay, D. Ambuel and L. Palumbo is devoted to ont.